Revolutionizing Payment Systems: Enhancing Speed, Security, and Cost Efficiency with Blockchain Technology - Elden, Moaz Ayman Gamal; Ismail, Ahmed Salama; Shaheen, Masoud E. (Journal of Posthumanism, 2025)
Payment systems have been known in recent years as one of the main achievements that caused a lot of significant evaluation but the transaction process is plagued by multiple roles that lead to prolonged delays, security vulnerabilities, and an extensive reconciliation period, ultimately undermining efficiency and trust. Also, the payment systems may experience failures or inefficiencies due to slowing processing time when using different third-party applications, which results in a slow running time, increased bank transaction costs, and payment processing fees. Hence, addressing and handling the common problems of payment systems has been conducted through this research by applying blockchain techniques. Then, the aim behind this work is to show how speed-up processing can lower costs through Blockchain’s decentralized environment through a peer-to-peer framework and improve security with cryptographic techniques that ensure transaction integrity and data authentication for more effective payment systems with an overall enhancement score to be 0.3125, demonstrating a measurable improvement over traditional systems. The findings highlight Blockchain’s potential to enhance payment efficiency, security, and cost-effectiveness, making it a viable solution for modern financial transactions.